Carbazolyl-bis(triazole) and Carbazolyl-bis(tetrazole) Complexes of Palladium(II) and Platinum(II). Issue 4 (23rd March 2021) - Samanta, Samya; Zheng, Cameron; Gajecki, Leah; Berg, David J.; Oliver, Allen G.; Crosby, Tristan; Godin, Logan; Sandhu, Jaylene
Abstract: The synthesis of several carbazole- bis (triazole) (CzTr R ) and carbazole- bis (tetrazole) (CzT R ) ligands (5a–d and 6a–d, respectively, where R =Me (a), i – Pr (b), Bz (c) and CH2 -2, 4, 6-C6 H2 Me3 (d)) is reported. Reaction of these ligands with PdCl2 in refluxing acetonitrile affords the complete series of square planar complexes, Pd(CzTr R )Cl (7a–d ) and Pd(CzT R )Cl (8a–d ). The analogous platinum complexes are prepared by deprotonation of ligand carbazole nitrogen under nitrogen followed by reaction with Pt(COD)Cl2 to give Pt(CzTr R )Cl (9b, 9d ) and Pt(CzT R )Cl (10b, 10d ). The X-ray structure of several ligands (5b, 5c, 6c ) and their metal complexes (8b, 8d, 9b ) are reported. Complexes 7–10d were examined by cyclic voltammetry and DFT calculations to shed light on their electronic structures. The Pd and Pt complexes of the same ligand (CzTr: 7d, 9d ; CzT: 8d, 10d ) showed very similar oxidation potentials suggesting the lowest oxidation is ligand based. In contrast, oxidations of the tetrazole complexes 7d and 9d were notably more difficult than the triazole complexes 8d and 10d . Both of these observations are supported by DFT calculations that indicate the HOMO is essentially carbazole π-bonding in character. Graphical Abstract: